Pengembangan Media Pembelajaran IPS Card Match Circle Untuk Kelas IV SDN 36 Ampenan - Juniarti, Winda; Affandi, Lalu Hamdian; Husniati, Husniati (Jurnal Literasi dan Pembelajaran Indonesia, 2021)
This study aims to develop Card Match Circle learning media that are suitable for use in social studies learning for grade IV in elementary school, to find out how to use media in social studies learning and to find out whether Card Match Circle media is effective in improving social studies learning outcomes. The type of research used is Research and Development (R&D). The research model used is the ADDIE model developed by Benny (2010: 125). In the first stage the average validation results by material experts obtained a score of 34 with an average of 4.25 where the value lies in the interval 3.40 > X 4.21 and the average validation of media experts in the first stage obtained a score of 52 with an average 4.72 where the value lies in the interval 3.40 > X 4.21 and the media validation in the second stage obtains an average score of 53 with a mean of 4.81 where the value lies in the interval X > 4.21 and the results student responses obtained an average total score of 245 with an average of 4.53 where the value lies in the interval X > 4.21. It can be concluded that the IPS card match circle learning media is very good so it is suitable to be used as a learning medium.